Character Building Through Learning Short Story Entitled "Bertengkar Berbisik (Argueing Whispering)": Micro Ethnography Study At SMP Negeri 3 Purworejo - Anifah, Siti (2012)
This study addressed to describe the kinds of character developed in short story entitled "Bertengkar Berbisik (Argueing whispering)" and the applications of character development through learning short story entitled "Bertengkar Berbisik (Argueing whispering)" in Class IX of SMP Negeri 3 Purworejo. It was a qualitative study using ethnography design. This study was done at SMP 3 Purworejo. Interviews were done to some informants, the principal, Indonesian teacher, and students. Data collection methods used were in-depth interview, observation, and documentation. Data analysis used an interactive model of analysis started by (1) data reduction, (2) data display, and (3) conclusion. To check the validity of data used credibility, transferability, dependability,a nd confirmability. The findings suggested that there were seven character values contained in the short story entitled "Bertengkar Berbisik (Argueing Wishpering)". The seven characters were religious, honest, responsibility, social care, tolerance, hard work, and democracy. Those seven characters were reflected through setting and characterization (sayings and actions) of the characters in the story. Character development was carried out through a process of learning story entitled "Bertengkar Berbisik (Argueing Whispering)". There were three steps taken by the teacher in the learning process of short story. First, put the value of the character in preparing the lesson plan. Second, use a variety of methods-lectures, discussion, and debate. Third are examples and creativity.